Transformasi Etika dalam Pelayanan Publik di Era Otonomi Daerah - Eka Sugiarti Setianingrum; Oja, Hubertus; Erwin Nugraha Purnama (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Public services are all activities to fulfill basic needs in accordance with the basic rights of every citizen to goods, services and/or administrative services provided by service providers. The task of central and regional governments is to provide public services that satisfy the community. Regional autonomy policies in Indonesia result in regional governments having responsibility and authority in determining minimum service standards. The fundamental problem in the service process is ethics. There are no standards regarding ethics and sanctions that specifically regulate violations committed by officials in public services. It is hoped that the granting of autonomy to district and city governments will be more responsive in responding to various problems developing in the regions so that development programs in meeting community needs become more effective. Regional governments through regional autonomy have great authority in determining policies, including policies regarding quality public services in accordance with the situation and conditions in the region. The changing demands and growing needs of society are changing the orientation of service quality. The quality of service is now determined by the community, not the government anymore. Thus, the assessment of service quality is not based on recognition from the service provider, but rather the service recipient (society).